Secondary structures for splice junctions in eukaryotic and viral messenger RNA precursors. - Trapnell, B C (1980)
Thermodynamically stable secondary structures have been found for adjacent splice junctions of 17 introns from 10 eukaryotic and viral mRNA precursors. Complementary regions in these structures position the exons to be ligated in a favourable orientation for splicing. The possible role of these structures in a general splicing mechanism in described.